Laser Speckle Contrast Imaging to Evaluate Bowel Lesions in Neonates with NEC - Knudsen, Kristine Bach Korsholm; Thorup, Joergen; Strandby, Rune Broni; Ambrus, Rikard; Ring, Linea Landgrebe; Ifaoui, Inge (European Journal of Pediatric Surgery Reports, 2017)
Background Necrotizing enterocolitis (NEC) is the most frequent surgical emergency in newborns. Intestinal ischemia is considered a factor that precedes the development of NEC lesions. Laser speckle contrast imaging (LSCI) can be used to assess tissue microcirculation. We evaluated if LSCI may help to detect intestinal regions with reduced microcirculation in NEC.Case Report A male patient (gestational age, 26 [3/7] weeks; birth weight, 600 g) showed clinical signs of NEC 28 days after birth. X-ray revealed pneumatosis intestinalis and portal gas. Laparotomy showed NEC lesions with signs of transmural ischemia in the terminal ileum and cecum. Surgical resection lines (RLs) were marked, followed by LSCI measurements and resection of the bowel between the two RLs. Post hoc LSCI analyses were conducted on both sides of the proximal and distal RL. Low-flux values, indicating reduced microcirculation, were found in the macroscopically assessed necrotic bowel at the proximal RL, whereas higher flux values, indicating sufficient microcirculation, were found in the macroscopically assessed normal bowel.Discussion This study is the first description of intra-abdominal use of LSCI to evaluate tissue microcirculation in relation to NEC lesions. LSCI could be a valuable tool to distinguish between ischemic and nonischemic bowel in neonates undergoing surgery for NEC.
Keywords: necrotizing enterocolitis; surgery; infant; microcirculation; ischemia